Business Success is Based on Self-Efficacy and Business Motivation - Fadly, Januar Nur Mohamad; Gemina, Dwi; Kartini, Tini (MultiTech Publisher, 2024)
Business success is an important thing that will influence the achievement of the goals of UMKM District Caring businessmen. Self-efficacy and business motivation are things that influence the success of Caringin District UMKM businesses, so it is appropriate for businessmen to pay attention to these things so that consumers are interested in making purchases so that business success will be achieved. This research aims to determine the influence of self-efficacy and business motivation on business success. The research method used is path analysis. The sampling technique in this research is probability sampling. The sample used was 100 UMKM businessmen in Caringin District. The results of the research show that simultaneously and partially the variables of self-efficacy and business motivation have a direct and positive effect on business success in Caringin District UMKM.